Untersuchungen am Kopf des fetalen Narwals Monodon monoceros: Ein Atlas zur Entwicklung und funktionellen Morphologie des Sonarapparates - Comtesse-Weidner, Pia; Justus Liebig University Giessen (My University, 2007)
Die vorliegende Arbeit beschreibt und dokumentiert am Beispiel des Narwals (Monodon monoceros) die Morphologie und Entwicklung der in der Kopfregion gelegenen potentiell sonarrelevanten Strukturen. Hierzu wurde anhand der einmaligen, lückenlosen histologischen Schnittserie eines Narwalfetus von 137 mm (NEF1) die gesamte Kopfregion als Entität lichtmikroskopisch untersucht und die hier interessierenden Details erfaßt. Der so entstandene Atlas bietet auf 86 ausgewählten Abbildungen die Möglichkeit, die Ontogenese, Morphologie und Topographie der relevanten Skelett- und Weichteil-Strukturen bei einem jungen Individuum nachzuvollziehen und dabei Hinweise auf deren Funktion zu erhalten. Diese Befunde wurden mit der existierenden Literatur über die Strukturen der Sonaremission und perzeption bei Zahnwalen verglichen und diskutiert. Im abschließenden evolutionsbiologischen Kapitel wurden zum besseren Verständnis der erhobenen Befunde die Entstehung der Zahnwale und ihre mannigfaltigen Anpassungen an den Lebensraum Wasser im Überblick dargestellt.Bei dem fetalen Narwal (NEF1) befindet sich eine Vielzahl der künftig im Dienste der Emission und Perzeption von Ultraschall stehenden Strukturen in einem fortgeschrittenen ontogenetischen Entwicklungsstadium, ohne jedoch histologisch ausgereift zu sein. So zeigen sämtliche Organsysteme prinzipiell eine Intermediärsituation zwischen dem späten Embryo, welcher morphologisch noch weitgehend dem Säugetierbauplan entspricht, und dem Neugeborenen, welches in seinen strukturellen Charakteristika (für Säugetiere) ungewöhnlich stark dem Adultstadium entspricht (extreme Nestflüchter-Problematik). Vor dem Hintergrund der Tatsache, daß sich evolutionäre Adaptationsprozesse von Säugetiergruppen während der fetalen Entwicklung in groben Zügen abbilden, ist bei dem untersuchten Narwalfetus NEF1 (analog zur frühen Anpassung der Wale an die physikalischen Bedingungen des Hörens unter Wasser) die Morphogenese der Temporalregion mit den Strukturen der Schallperzeption bereits weitgehend abgeschlossen.

This work describes and reveals the morphology and evolution of the potential sonar relevant structures in the fetal narwhal (Monodon monoceros) which are located in the forehead. For this purpose a unique section of microslide series of an early narwhal fetus of 137 mm total length was investigated in order to determine the morphological status of those structures which are presumably part of the sonar system. On 86 selected figures the atlas offers the possibility to recall the ontogenesis, morphology and topography of relevant osseous and soft tissue structures on the basis of a very young individuum. The results were compared and discussed with the present literature about biosonar emission and perception in toothed whales. The concluding chapter about the evolutionary biology of toothed whales and their various adaptations to the habitat water serves for a better comprehension of the gained results.In the fetal narwhal many of the future sonar relevant structures seem to be in an advanced ontogenetic stage without being histologically mature. In principle, the morphology of this narwhal fetus is intermediate between the late embryo according to the mammalian bauplan and the neonate condition. Due to the fact that mammals passed through evolutionary adaptation processes during their fetal development, the investigated narwhal fetus NEF1 (analog the early adaptation of toothed whales to the physically conditions of hearing under water) has already completed the morphogenesis of the temporal region where the structures of sound perception are located. The most important observations for the relative maturity and the toothed-whale-character of the fetus are as follows:- rudimentary external auditory meatus, tympanic membrane present;- large Tympanoperoticum in particular the periotc with the cochlea;- large and compact ear ossicles;- uncoupling of periotic incomplete and rotation of cochlea complete;- vestibular apparatus very small particularly the Canalis semicircularis;- modification of the mastication muscles: jugal bone thinned-out an rod-like, reduction of Musculus masseter;- dental with large alveolar canal, containing future mandibular fat body (sound channel);- mandibular fat body in contact with the tympanoperiotic;Signs of absent maturity are:- Meckel s cartilage merge into Malleus;- Tympanic bone clasp-like;- Cavum tympani small, Ossicula auditiva surrounded by mesenchym;- no tympanic air sacs;- telescoping of skull in early stage.Some structures of sound generation (monkey lips / dorsal bursae complex, MLDB) are not clearly to identify, others could only assume to be anlagen (Primordium) of those structures. The so called monkey lips or phonic lips (Cranford et al. 1996), which are normally found in sectioned toothed whales, could not be identified in the fetal narwhal NEF1, but the nasal plugs are present. The nasal air sacs are present as buds in both sides of the nasal cavity. The future melon another large acoustic fat body consists of mesenchyme; lamination or segmentation of the facial musculature (= blow-hole musculature) is not detectable.Generally the structures of the temporal region seem to bo more mature then the structures of the nasal complex. Structures of the nasal complex linked together with the phenomenon of the telescoping effect (enlargement of the rostrum and its components) that occurs in the early evolution of toothed whales and just started in the fetal narwhal NEF1.The abundance of anatomical peculiarities in the head region of odontocetes demonstrates the profund adaptations of former fossil ungulates to a submarine life and point out the impressive synorganisation of the sonar system from two formerly seperated complexes (ancient temporal region with the ear complex and recent nasal region with the epicranial complex). The significant amount of adaptations enabled the odontocetes to establish a perfect information system for orientation, hunting and communication under water.
Investigations on the head of the fetal narwhal Monodon monoceros
Keywords: Zahnwale; Biosonar; Narwal; Sonarapparat; Fetus; ddc:630